The Anti-public administration presidency: the damage Trump has wrought - Goodsell, Charles T. (American Review of Public Administration)
President Trump and his Administration have gravely damaged the institutions and values of American public administration. Harm has been done to the federal workforce, the policymaking process, the integrity of missions, agencies and programs, and the government$1 (Bs relation to science. - Reproduced.s
Keywords: Bureaucracy; United States - Politics and government